Percepções sobre sexualidade e gênero de professoras no ensino de ciências: um estudo de caso - Marques, Jéssica Karine (Universidade Federal de São Carlos, 2020)
Sexuality education is a controversial topic and, at the same time, it is considered a taboo by society. Systematically, the theme has been discussed in different ways and nomenclatures by the public authorities, by social movements and media and in formal, non-formal and informal spaces, when talking about education. The objective of this research was to understand what are the teachers' perceptions about gender, sexuality and their relations in Science Teaching in a public elementary school II and how these perceptions interfere in the approach of this theme in the classroom. We carried out a case study and the tools used to carry out the research were: semi-structured interviews with school teachers; analysis of the School's Pedagogical Political Project (PPP) and the textbook used; analysis of didactic sequences that dealt with the topic directly or indirectly. We use Discursive Textual Analysis (DTA) as an interpretative and analytical tool for the data collected, since this work aimed to deepen the understanding of the investigated phenomena from a rigorous and judicious analysis. After the transcripts of the interviews and the unification of the speeches, we arrived at two categories: aspects of the teaching profession and aspects related to the content. The research showed that the teachers interviewed did not have specific discussions about sexuality and gender in initial and continuing education. According to the interviewees, they discuss in class what is geared towards anatomy and physiology, that is, characteristics, organ functioning, reproduction and STIs. However, the literature indicates the need for training that is guided by an understanding in which sexuality is worked in a way that goes beyond biological determinism, thus, it is possible to open spaces for discussions about sexuality in the cultural and social field, understanding gender inequalities in order to combat discrimination and violence.
Perceptions about sexuality and gender of teachers in science teaching: a case study
Keywords: Gênero; Sexualidade; Formação continuada; Ensino de ciências; Gender; Sexuality; Continuing formation; Science teaching; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS